PREDICTION OF THE SUM OF NEW FAMILY PLANNING ACCEPTORS IN THE IMPACT OF THE COVID-19 PANDEMIC: A STUDY USING THE ARIMA MODEL - Shindy Ayudia Darista; Kurnia Ilahi; Mahmudah (Jurnal Biometrika dan Kependudukan, 2024)
The sum of new Family Planning (KB) acceptors in Pamekasan Regency decreased from March to April 2020 due to the COVID-19 pandemic. This decline will hinder the increase in achieving the Modern Contraceptive Prevalence Rate (mCPR) as the target of the 2020-2024 National Medium Term Development Plan (RPJMN), so modelling is needed to predict the sum of new family planning acceptors in Pamekasan Regency. This research aims to predict the sum of new family planning acceptors in Pamekasan Regency using the ARIMA model. This research is a non-reactive quantitative research. The unit of analysis for this research is all-new monthly family planning acceptors in Pamekasan Regency. The data used is the number of new monthly family planning acceptors from January 2016 to December 2021, sourced from the Pamekasan Regency Women's Empowerment, Child Protection and Family Planning Service. The research results show that the best model for predicting the number of new family planning acceptors in Pamekasan Regency is ARIMA [1,1,1] with the equation 0.0011(B)11Zt=0.006+0.0001(B)at. Prediction results using the ARIMA model [1,1,1] show that the number of new family planning acceptors tends to increase in January-December 2022. The sum of new family planning acceptors shows an increasing pattern, but the increase does not reflect the impact of the end of the COVID-19 pandemic.